Calculation of the Cost of Production of Candied Carica at the Exotic Umkm in Dieng, Wonosobo, Central Java - Muhamad Nur Rizqi; Hurriyaturrohman Hurriyaturrohman; M. Imam Sundarta; Yudiana Yudiana (LPPM UIKA Bogor, 2022)
The purpose of holding this community service is to facilitate understanding and solving a little problem experienced by MSMEs in general and Exotic Dieng MSMEs in particular. The concern of this community service is the calculation of the Cost of Goods Manufactured for products that are quite popular with domestic and foreign tourists. The method used in accompanying the calculation of the cost of goods manufactured is the Full Costing method with the addition of the Joint cost allocation method, this is done because these MSMEs still combine production costs, cannot separate various types of costs, and have not understood the importance of allocation to joint costs incurred so that the cost of goods mentioned is only a range without a certainty. The results obtained about the cost of goods of candied Carica cup packaging and glass bottle packaging are Rp. 1,333.28 and Rp. 7,204.51, respectively. With the use of the full costing method in determining the cost of goods manufactured and the joint cost allocation method, it is clear the number of production costs obtained. Although the results obtained are smaller than the range stated by the owner of this MSME, we are of the view that there should still be a review of the calculations that have been obtained at least once a year, this is a form of vigilance or beware of inflation, especially in raw material.